INCREASING INDONESIAN SPEAKING SKILLS USING THE APPLICATION OF THE DEEP DIALOGUE LEARNING MODEL THROUGH A SCIENTIFIC APPROACH - Hanafi; Tuti Asiyah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Students' speaking skills are still low, students tend to be silent and inactive in learning Indonesian. The purpose of this study was to determine the application of the Deep Dialogue learning model to increase students' speaking skills in Indonesian language subjects. at class III MI An-Nahwa. The research method used Classroom Action Research (CAR) Kemmis Taggert's model. This classroom action research was carried out in two cycles, each cycle consisting of planning, action, observation, and reflection. The result of this research is that the use of Deep Dialogue learning model through a scientific approach can improve students' speaking skills in learning Indonesian. This can be seen from the average score and the activities of students in learning more active. It can be seen from the activities of pre-cycle, cycle I and cycle II. The improvement in student skills and learning outcomes in the pre-cycle gets an average score of 64.08 with 36% learning completeness, in the first cycle the average value of students learning outcomes are 73.68 with learning mastery 60%, and in the second cycle the average value of student learning outcomes is 83.04 with learning mastery reached 88%.